Disinformation in the Brazilian pre-election context: probing the content, spread and implications of fake news about Lula da Silva - Dourado, Tatiana (2021)
This research scrutinizes the content, spread, and implications of disinformation in Brazil’s 2018 pre-election period. It focuses specifically on the most widely shared fake news about Lula da Silva and links these with the preexisting polarization and political radicalization, ascertaining the role of context. The research relied on a case study and mixed-methods approach that combined an online data collection of content, spread, propagators, and interactions’ analyses, with in-depth analysis of the meaning of such fake news. The results show that the most successful fake news about Lula capitalized on prior hostility toward him, several originated or were spread by conservative right-wing politicians and mainstream journalists, and that the pro-Lula fake news circulated in smaller networks and had overall less global reach. Facebook and WhatsApp were the main dissemination platforms of these contents.